Early Discipline Behavior: Read aloud Story with Big Book Media - Eka, Eka Pratiwi; Dhieni, Nurbiana; Supena, Asep (Jurnal Pendidikan Usia Dini, 2020)
Disciplinary behavior increases children's responsibility and self-control skills by encouraging mental, emotional and social growth. This behavior is also related to school readiness and future academic achievement. This study aims to look at read aloud with the media of large books in improving disciplinary behavior during early childhood. Participants were 20 children aged 5-6 years. By using qualitative methods as a classroom action research, data collection was carried out by observation, field notes, and documentation. The results of pre-cycle data showed that the discipline behavior of children increased to 42.6%. In the first cycle of intervention learning with ledger media, the percentage of children's discipline behavior increased to 67.05%, and in the second cycle, it increased again to 80.05%. Field notes found an increase in disciplinary behavior because children liked the media which was not like books in general. However, another key to successful behavior of the big book media story. Another important finding is the teacher's ability to tell stories to students or read books in a style that fascinates children. The hope of this intervention is that children can express ideas, insights, and be able to apply disciplinary behavior in their environment. Keywords: Early Discipline Behavior, Read aloud, Big Book Media References Aksoy, P. (2020). The challenging behaviors faced by the preschool teachers in their classrooms, and the strategies and discipline approaches used against these behaviors: The sample of United States. Participatory Educational Research, 7(3), 79–104. https://doi.org/10.17275/per.20.36.7.3 Anderson, K. L., Weimer, M., & Fuhs, M. W. (2020). Teacher fidelity to Conscious Discipline and children’s executive function skills. Early Childhood Research Quarterly, 51, 14–25. https://doi.org/10.1016/j.ecresq.2019.08.003 Andriana, E., Syachruroji, A., Alamsyah, T. P., & Sumirat, F. (2017). Jurnal Pendidikan IPA Indonesia Natural Science Big Book With Baduy Local Wisdom Base. 6(1), 76–80. https://doi.org/10.15294/jpii.v6i1.8674 Aulina, C. N. (2013). Penanaman Disiplin Pada Anak Usia Dini. PEDAGOGIA: Jurnal Pendidikan, 2(1), 36. https://doi.org/10.21070/pedagogia.v2i1.45 Bailey, B. A. (2015). Introduction to conscious discipline Conscious discipline: Building resilient classrooms (J. Ruffo (ed.)). Loving Guidance, Inc. Brown, E. (1970). The Bases of Reading Acquisition. Reading Research Quarterly, 6(1), 49. https://doi.org/10.2307/747048 Clark, S. K., & Andreasen, L. (2014). Examining Sixth Grade Students’ Reading Attitudes and Perceptions of Teacher Read Aloud: Are All Students on the Same Page? Literacy Research and Instruction, 53(2), 162–182. https://doi.org/10.1080/19388071.2013.870262 Colville-hall, S., & Oconnor, B. (2006). Using Big Books: A Standards-Based Instructional Approach for Foreign Language Teacher CandidatesinaPreK-12 Program. Foreign Language Annals, 39(3), 487–506. https://doi.org/doi:10.1111/j.1944-9720.2006.tb02901.x Davis, J. R. (2017). From Discipline to Dynamic Pedagogy: A Re-conceptualization of Classroom Management. Berkeley Review of Education, 6. https://doi.org/10.5070/b86110024 Eagle, S. (2012). Computers & Education Learning in the early years : Social interactions around picturebooks , puzzles and digital technologies. Computers & Education, 59(1), 38–49. https://doi.org/10.1016/j.compedu.2011.10.013 Farrant, B. M., & Zubrick, S. R. (2012). Early vocabulary development: The importance of joint attention and parent-child book reading. First Language, 32(3), 343–364. https://doi.org/10.1177/0142723711422626 Galini, R., & Kostas, K. (2014). Practices of Early Childhood Teachers in Greece for Managing Behavior Problems: A Preliminary Study. Procedia - Social and Behavioral Sciences, 152, 784–789. https://doi.org/10.1016/j.sbspro.2014.09.321 Ho, J., Grieshaber, S. J., & Walsh, K. (2017). Discipline and rules in four Hong Kong kindergarten classrooms : a qualitative case study. International Journal of Early Years Education, 1–15. https://doi.org/10.1080/09669760.2017.1316242 Hoffman, L. L., Hutchinson, C. J., & Reiss, E. (2005). Training teachers in classroom management: Evidence of positive effects on the behavior of difficult children. In The Journal of the Southeastern Regional Association of Teacher Educators (Vol. 14, Issue 1, pp. 36–43). Iraklis, G. (2020). Classroom (in) discipline: behaviour management practices of Greek early childhood educators. Education 3-13, 0(0), 1–9. https://doi.org/10.1080/03004279.2020.1817966 Kalb, G., & van Ours, J. C. (2014). Reading to young children: A head-start in life? Economics of Education Review, 40, 1–24. https://doi.org/doi:10.1016/j.econedurev.2014.01.002 Kemmis, S., & McTaggart, R. (1988). The action research planner (3rd ed.). Deakin University Press. Ledger, S., & Merga, M. K. (2018). Reading aloud: Children’s attitudes toward being read to at home and at school. Australian Journal of Teacher Education, 43(3), 124–139. https://doi.org/10.14221/ajte.2018v43n3.8 Longstreth, S., Brady, S., & Kay, A. (2015). Discipline Policies in Early Childhood Care and Education Programs : Building an Infrastructure for Social and Academic Success Discipline Policies in Early Childhood Care and Education Programs : Building an Infrastructure. Early Education and Development, 37–41. https://doi.org/10.1080/10409289.2011.647608 Mahayanti, N. W. S., Padmadewi, N. N., & Wijayanti, L. P. A. (2017). Coping With Big Classes: Effect of Big Book in Fourth Grade Students Reading Comprehension. International Journal of Language and Literature, 1(4), 203. https://doi.org/10.23887/ijll.v1i4.12583 Martha Efirlin, Fadillah, M. (2012). Penanaman Perilaku Disiplin Anak Usia 5-6 Tahun di TK Primanda Untan Pontianak. Pendidikan Anak Usia Dini, 1–10. Merga, Margaret K. (2017). Becoming a reader: Significant social influences on avid book readers. School Library Research, 20(Liu 2004). Merga, Margaret Kristin. (2015). “She knows what I like”: Student-generated best-practice statements for encouraging recreational book reading in adolescents. Australian Journal of Education, 59(1), 35–50. https://doi.org/10.1177/0004944114565115 Merga, Margaret Kristin. (2017). Interactive reading opportunities beyond the early years: What educators need to consider. Australian Journal of Education, 61(3), 328–343. https://doi.org/10.1177/0004944117727749 Milles;, M. B., & Huberman, M. (2014). Qualitative Data Analysis. Sage Publications. Moberly, D. A., Waddle, J. L., & Duff, R. E. (2014). Journal of Early Childhood Teacher Education The use of rewards and punishment in early childhood classrooms The use of rewards and punishment in early childhood classrooms. Journal of Early Childhood Teacher Education, 37–41. https://doi.org/10.1080/1090102050250410 Mol, S. E., & Bus, A. G. (2011). To Read or Not to Read: A Meta-Analysis of Print Exposure From Infancy to Early Adulthood. Psychological Bulletin, 137(2), 267–296. https://doi.org/10.1037/a0021890 Pegg, L. A., & Bartelheim, F. J. (2011). Effects of daily read-alouds on students’ sustained silent reading. Current Issues in Education, 14(2), 1–8. Penno, J. F., Wilkinson, I. A. G., & Moore, D. W. (2002). Vocabulary acquisition from teacher explanation and repeated listening to stories: Do they overcome the Matthew effect? Journal of Educational Psychology, 94(1), 23–33. https://doi.org/10.1037/0022-0663.94.1.23 Septyaningrum, A., & Mas’udah. (2015). Pengaruh metode bercerita berbasis dongeng terhadap kedisiplinan anak. Fakultas Ilmu Pendidikan, 1–5. Swanson, E., Vaughn, S., Wanzek, J., Petscher, Y., Heckert, J., Cavanaugh, C., Kraft, G., & Tackett, K. (2011). A synthesis of read-aloud interventions on early reading outcomes among preschool through third graders at risk for reading difficulties. Journal of Learning Disabilities, 44(3), 258–275. https://doi.org/10.1177/0022219410378444 Turan, F., & Ulutas, I. (2016). Using storybooks as a character education tools. Journal of Education and Practice, 7(15), 169–176. Turuini Ernawati, Rasdi Eko Siswoyo, Wahyu Hardyanto, T. J. R. (2018). Local- Wisdom-Based Character Education Management In Early Childhood Education. The Journal Of Educational Development. Westbrook, J., Sutherland, J., Oakhill, J., & Sullivan, S. (2019). ‘Just reading’: the impact of a faster pace of reading narratives on the comprehension of poorer adolescent readers in English classrooms. Literacy, 53(2), 60–68. https://doi.org/10.1111/lit.12141 Yılmaz, S., Temiz, Z., & Karaarslan Semiz, G. (2020). Children’s understanding of human–nature interaction after a folk storytelling session. Applied Environmental Education and Communication, 19(1), 88–100. https://doi.org/10.1080/1533015X.2018.1517062 Zachos, D. T., Delaveridou, A., & Gkontzou, A. (2016). Teachers and School “Discipline” in Greece: A Case Study. European Journal of Social Sciences Education and Research, 7(1), 8. https://doi.org/10.26417/ejser.v7i1.p8-19